Functional analysis of a novel transmembrane protein, P1xdc2, in the developing nervous system of the chick and mouse - Miller, Suzanne F. C. (Trinity College (Dublin, Ireland). Department of Genetics, 2009)
Studies utilising the PLAP secretory trap method isolated a gene trap insertion in a novel gene (mouse line KST37) (Leighton et al., 2001) which has since been named Plexin domain containing 2 (Plxdc2). Plxdc2 encodes a novel transmembrane protein with an expression pattern and architecture suggestive of a role in axon guidance and development of the brain. In addition to a region of nidogen homology, the Plxdc2 protein contains a plexin repeat, a domain found in known axon guidance molecules such as Semaphorins and Plexins.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin.